Le Photomontage comme incarnation du projet d’architecture : le Frac de Dunkerque, Lacaton & Vassal, 2009-2013 - Oscar Barnay (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The article aims to highlight the particularities of photomontage as a representation of the architectural project, using photography as a supporting image. It develops an image analysis of a photomontage produced by the architects Lacaton & Vassal in the context of the competition for the construction of the FRAC Grand-Large, in Dunkirk, France, 2009. Through this examination, the following issues are addressed: the indiciality of the photographs used as a support for the photomontages, the way in which the image registers deployed by a photomontage can be presented as embodiments of an architectural project. Thus, the images become both representations and metaphors of the project, capable of serving the architects’ purpose.